Evaluating fondaparinux vs bovine-derived enoxaparin as halal anticoagulants in East Java Provincial Haji Hospital - Samlan, Karima; Ayumuyas, Nur Palestin; Ramdani, Dewi; Zulfiana, Risa; Sari, Annisa Kartika; Isnaeni, Isnaeni (Journal of Halal Science and Research, 2025)
This study evaluated the effectiveness of two halal anti-coagulant therapies used in patients at East Java Provincial Haji Hospital. The research design was a retrospective, comparative, observational study spanning the last three years. The study population consisted of patients assigned to anti-coagulant therapy, divided into two groups based on the use of two halal anti-coagulants: bovine enoxaparin and fondaparinux. Participation in this study is voluntary, and all patient data will be kept confidential in accordance with data protection laws. Inclusion criteria were patients with diagnoses requiring anticoagulants, such as atrial fibrillation, while exclusion criteria included patients with conditions that could affect drug metabolism or response to therapy. The main variables to be assessed in this study were length of stay, which is one of the key indicators of anticoagulant effectiveness. In addition, this study also compared the cost-effectiveness of hospital care. This data will be collected through electronic medical records, followed by rigorous statistical analysis. Independent t-test and chi-square by which quantitative data, while multivariate analysis was applied to control potential confounding variables. Two anticoagulant groups were used as samples containing fondaparinux and bovine enoxaparin, respectively. Based on the observational results showed that the average length of stay for patients using the group fondaparinux was shorter than bovine enoxaparin. The bovine enoxaparin group has a lower price per dose, but based on the LOS, the fondaparinux group can reduce total hospital costs, because it has a shorter length of stay. The expectation of this research will provide insight into the effectiveness of halal anti-coagulant drugs in muslim patients, which will also assist in clinical decision making. Hopefully, the results of this research will be useful in Indonesia and other countries with large muslim populations, and can provide the scientific confirmation needed to validate the use of halal medicines. Keywords: Anticoagulant, Effectiveness, Enoxaparin, Fondaparinux, Halal pharmaceuticals.